Intravenous nitrates in modern cardiology - I. V. Zhirov; S. N. Tereshchenko (Кардиоваскулярная терапия и профилактика, 2005)
Nitrates are widely used in cardiology since XIX century. In modern urgent cardiology, intravenous nitrates are administered most often. Numerous studies confirm high clinical efficacy and safety of intravenous nitrates in acute coronary syndromes, acute heart failure, or acute decompensation of chronic heart failure.